2019
DOI: 10.1242/bio.041293
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 50 Hz magnetic field at 100 µT exert no DNA damage in cardiomyocytes

Abstract: The effects of exposure to magnetic fields (MFs) at electric frequencies (50–60 Hz) on carcinogenicity are still in debate. Whether exposure to MFs affects the heart is also a debated issue. This study aimed to determine whether exposure to extremely low frequency MFs (ELF-MFs) induced DNA damage in cardiomyocytes both in vitro and in vivo. Human ventricular cardiomyocytes were exposed to 50 Hz ELF-MF at 100 µT for 1 h continuously or 75 min intermittently. The effects of the treatments were evaluated by DNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
9
0
4
Order By: Relevance
“…Therefore, different experiments with various examinations should be designed to test and verify the effects of EMF exposure on the cardiovascular system. Previously, we found that 100 µT EMF, which is the threshold of public exposure, did not affect the cardiovascular system and other organs (4,(23)(24)(25)(26). In the current study, we elevated the intensity to 500 µT, which is the threshold of occupational exposure, to explore whether it would exert damages in the cardiovascular system in rats.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Therefore, different experiments with various examinations should be designed to test and verify the effects of EMF exposure on the cardiovascular system. Previously, we found that 100 µT EMF, which is the threshold of public exposure, did not affect the cardiovascular system and other organs (4,(23)(24)(25)(26). In the current study, we elevated the intensity to 500 µT, which is the threshold of occupational exposure, to explore whether it would exert damages in the cardiovascular system in rats.…”
Section: Introductionmentioning
confidence: 74%
“…In 2016, our group found that exposure to a 50-Hz EMF at 100 µT for 24 weeks did not show any obvious effects on the cardiovascular system in Sprague-Dawley (SD) rats (23). Recently, we also found that 1 h continuous or 75 min intermittent exposure to a 50-HZ EMF at 100 µT caused no DNA damage in cardiomyocytes derived from both humans and rats (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exposure system was identical to that described previously [Ruan et al, 2019;Wang et al, 2019]. The exposure system consisted of an exposure device and a plastic rack.…”
Section: Exposure Systemmentioning
confidence: 99%
“…ABSTRACTFirst Person is a series of interviews with the first authors of a selection of papers published in Biology Open, helping early-career researchers promote themselves alongside their papers. Yong Wang is first author on ‘Exposure to a 50 Hz magnetic field at 100 µT exerts no DNA damage in cardiomyocytes’, published in BiO. Yong is a PhD student in the lab of Dr Chen at the Huazhong University of Science and Technology, Wuhan, China, investigating cardiovascular pathophysiology.…”
mentioning
confidence: 99%